Dietary Habits of Older Adults in Serbia: Findings From the National Health Survey - Stosovic, Dragana M.; Vasiljevic, Nadja; Jovanovic, Verica; Cirkovic, Andja; Paunovic, Katarina; Davidovic, Dragana (Frontiers in Public Health, 2021)
Objectives: Adults aged 65 years and older comprise one fifth of the Serbian population. Many of them have multiple, often diet-related comorbidities. We aimed to investigate their dietary habits by comparing them with younger adults’ and to determine the relation of the differing ones to demographic, socioeconomic and health factors. Methods: We performed a secondary analysis of 2013 Serbian National Health Survey data on 14,082 adults. Binary logistic regression was used to determine dietary habits associated with older age (≥65 years) compared to younger age (18-64 years) and to assess their independent predictors in older adults. Results: Older adults more often reported everyday breakfast (OR=2.085, 95%CI=1.622-2.680) and brown/wholegrain bread consumption (OR=1.681, 95%CI=1.537-1.839), while using margarine (OR=0.578, 95%CI=0.397-0.839), discretionary salt (sometimes: OR=0.648, 95%CI=0.596-0.705, almost always: OR=0.522, 95%CI=0.445-0.614) and consuming fish (two or more times a week: OR=0.465, 95%CI=0.383-0.566) less frequently than younger adults. This was mainly positively related to urban environment, affluence, higher education and poor health. Conclusion: Using nationally representative data, we found that older adults reported healthier dietary habits compared to younger adults, which requires timely public health action.